PENGARUH EFEKTIVITAS KOMITE AUDIT, REPUTASI AUDITOR, SPESIALISASI AUDITOR TERHADAP AUDIT REPORT LAG - Tsaniya Nisya Fasha; Dwi Ratmono (Diponegoro Journal of Accounting, 2022)
This study was conducted to determine the effect of audit committee effectiveness, auditor reputation, and auditor specialization on audit report lag (ARL). In the study of the audit committee expertise, the number of audit committee members, audit committee meetings, audit committee charter, auditor reputation, and auditor specialization act as independent variables. The control variables used in this study are auditor rotation, company size, and profitability. In addition, the dependent variable in this study is audit report lag.The samples in the study were all companies listed on the IDX in 2019-2020 with a total sample of 1192 samples. The sample selection was based on the purposive sampling method with the criteria and requirements determined by the researcher. The analytical method used in this study is panel data regression analysis.The results of hypothesis testing show that the overall research year (2019-2020) audit committee expertise, number of audit committee members, audit committee meetings, auditor reputation, and company size have a significant negative impact on audit report lag. While the audit committee charter, auditor specialization, auditor turnover, and profitability have no effect on audit report lag. In addition, the results show that before the pandemic (2019), audit committee expertise, number of audit committee members, audit committee charter, auditor reputation, company size, and profitability had a significant negative impact on audit report lag. Meanwhile, audit committee meetings, auditor specialization, and auditor turnover have no effect on audit report lag. However, the results shown during the pandemic (2020) were only auditor reputation which had a significant negative effect on audit report lag. Meanwhile, audit committee expertise, number of audit committee members, audit committee meetings, audit committee charter, auditor specialization, auditor turnover, company size, and profitability have no effect on audit report lag.